Information Technology Integration Effect on Operational Performance of Kenya’s Public Health Sector - Anne W Mbugua; Juliana Namada (Integrated Journal of Business and Economics (IJBE), 2019)
The purpose of the research is to examine the effect of information technology integration on the operational performance of the of Kenya’s public health sector level five hospitals in Kenya. The study examined the moderating role of public procurement to the relationship between information technology integration and operational performance. To test the extent of information technology integration and relationship with the operational performance of level five hospitals in Kenya was empirically tested utilizing a causal, non-experimental, and cross-sectional research design. Regression analysis was carried out based on data from 164 respondents. In general, the study results support the idea that information technology integration has a significant effect on operational performance (β1=0.411, p <0.05) with R2 of 0.449 implying that 44.9% of the variation of operational performance is attributed to information technology integration. Information technology integration is vital in coordinating the SCI dimensions leading to the improved operational performance of the health facilities. It finds that public procurement mediates the relationship between information technology integration and operational performance of the health sector as it is an enabler of improved working relationships with the suppliers.